A catastrophic cause of chest pain - Sheikh, Azeem S (Clin Med (Lond), 2013)
Chest pain can be a manifestation of aortic pathology and must be considered in any patient with a history of chest trauma, hypertension, atherosclerosis, connective tissue disorder and/or radiographically abnormal aortic contours. Acute intramural haematoma can resemble acute myocardial infarction and can be life-threatening if not correctly diagnosed. Electrocardiogram (ECG) must be carried out in all patients as it helps distinguish acute myocardial infarction (for which antiplatelets and anticoagulants may be life-saving) from intramural haematoma (for which these drugs may be detrimental). Other imaging modalities may be considered depending upon the clinical situation.